(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Entrepreneurs have received significant media attention in several regions of the world in recent years. The quantity of startups in India is seeing a significant surge, and there is now a greater availability of investment across all sectors. In January 2016, the Indian government launched the Startup India programme, which has fundamentally transformed the perception of start-ups among markets, prospective entrepreneurs, and investors. This paper examines the current condition of the Indian startup ecosystem, identifies the obstacles that these businesses face, and describes the foundations that sustain them.